Real world data on light chain cardiac amyloidosis: Still a delayed diagnosis - Chatzileontiadou, Sofia; Zegkos, Thomas; Frouzaki, Christina; Apsemidou, Athanasia; Efthimiadis, Georgios; Parcharidou, Despoina; Papaioannou, Maria (Frontiers in Oncology, 2022)
Cardiac amyloidosis (CA) represents a myocardial disorder developed by fibril deposition of a heterogeneous group of misfolding proteins. Despite being rare, a high clinical index of suspicion and novel advanced diagnostic methods seem to facilitate its early recognition. Currently nine types of cardiac amyloidosis have been described with AL and ATTR being the most common. Light chain amyloidosis (AL) is a life-threatening disease, resulting from clonal plasma cells that produce amyloidogenic light chain fragments causing organ damage including the heart. Morbidity and mortality of these patients is strongly associated with the severity of cardiac involvement. Thus, early and precise diagnosis is crucial for prompt treatment initiation. In this study, we retrospectively analyzed data of 36 consecutive patients who were diagnosed with AL amyloidosis and treated in our center over the past 15 years. Heart involvement was present in 33 (92%) of them while 75% had severe cardiac disease as of stage IIIa and IIIb, according to the modified Mayo clinic staging system. Almost one third of these patients experienced an early death occurring the first five months of diagnosis. To capture everyday clinical practice, we provide details on clinical presentation, diagnostic challenges, and outcome of these patients.